Higher Order Thinking Skills Pada Penilaian Sumatif Dosen Program Studi Pendidikan Bahasa Indonesia - Ermawati E; Desy Rufaidah; Surmawati S (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
Summative assessment should not only give students the opportunity to demonstrate their conceptual understanding, but also provide opportunities for students to think critically as they apply their understanding under new conditions to solve new problems or to explain new phenomena. Critical thinking through the stages of remembering, understanding, applying, analyzing, evaluating, and creating is a student's cognitive stage. This study describes a summative assessment instrument based on Higher Order and Thinking Skills (HOTS) made by lecturers of the Indonesian Language and Literature Education Study Program. This research is a descriptive research. The population of this study was 27 lecturers of PBSI FKIP Universitas Sarjanawiyata Tamansiswa Yogyakarta in the odd semester of 2021/2022. The research sample consisted of 8 summative assessments from lecturers of language family, literature group, teaching group, Faculty Course, and University Course. The data and data sources used are summative assessment instruments used for the 2020/2021 Even Semester Final Examination. Data analysis technique with interactive analysis of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions or verification. The results show that from … samples, obtained … items. From … items, … questions are HOTS (68.8%) and … questions are not HOTS (32.2%). The instrument questions that were made did not meet the HOTS due to the following reasons. 1). 2); 2; 3). Therefore, …